Non-contiguous finished genome sequence and description of Anaerococcus provenciensis sp. nov. - Pagnier, Isabelle (Michigan State University, 2014)
Anaerococcus provenciensis strain 9402080(T) sp. nov. is the type strain of A. provenciensis sp. nov., a new species within the genus Anaerococcus. This strain was isolated from a cervical abscess sample. A. provenciensis is a Gram-positive anaerobic cocci. Here, we describe the features of this organism, together with the complete genome sequence and annotation. The 2.26 Mbp long genome contains 2099 protein-coding and 57 RNA genes including 8 rRNA genes and exhibits a G+C content of 33.48%.